AMERICAN POET AT USM FOR CREATIVE WRITING WORKSHOP - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 31 March 2017 A visit by an American poet and spoken word artist, Baraka Blue, was made possible recently with the collaboration between the Universiti Sains Malaysia (USM) School of Languages, Literacies and Translation (SoLLaT), the United States Embassy of Kuala Lumpur and Crescent Collective.